Influence of Financial Compensation on Employee Performance at PT. Bank BTPN, Padang City - Weni Yuliani; Lisa Hendriani; Novendra Halim (CV. HEI PUBLISHING INDONESIA, 2024)
Subtle skills relate to each person's ability to communicate and behave with others. These abilities include the ability to communicate, provide a variety of solution options, and decide on the best solution (Melati, 2023). This is the method that PT BANK BTPN Kota Padang needs to get a workforce that can help the growth and progress of the company. Based on the previous background, the author tries to examine how to improve compensation in labor management that can help the operations of PT BANK BTPN Kota Padang. The author examines this problem with the title